The Impact of Business Intelligence Systems in Reducing the Risks of Electronic Accounting Information Systems: The Modifying Role of Enterprise Resource Planning Systems A Field Study: Jordanian Telecommunications and Information Technology Companies - Akram Al-Qudah, Laith; Sulaiman Malahim, Sari; Ahmed Alatyat , Zakarya; Ahmad Ateiah, Mousa; Mohammed Al-Qudah, Abdallah (Jordan Journal of Business Administration, 2025)
This study aimed to identify the impact of business intelligence systems with their various elements (collection, analysis, and storage of data; adequacy of strategic techniques; business performance management; and competitive intelligence) in reducing the risks of electronic accounting information systems in Jordanian telecommunications and information technology companies, and the study also aimed to identify the role of enterprise resource planning (ERP) systems in determining the relationship between business intelligence systems and electronic accounting information systems in the surveyed companies. The study population consisted of all Jordanian telecommunication and information technology companies, which numbered (65) companies, where the purposeful sample method was used by publishing an electronic questionnaire (online questionnaire) via the Google Form website, addressed to financial managers, their assistants, department heads and supervisors, and (217) responses were received. The data was subjected to statistical analysis. The study found that business intelligence systems with their various elements reduce the risks of electronic accounting information systems in Jordanian telecommunications and information technology companies, and the study also found that business intelligence systems with their combined elements reduce the risks of electronic accounting information systems with the presence of enterprise resource planning systems as a modifying variable in the companies investigated. The study recommended that telecommunication and information technology companies focus on providing qualified integrated teams with the ability to receive the service and implement the ERP system efficiently.